Perception of worsening health predicts mortality in older men: The Health in Men Study (HIMS) - Alfonso, Helman; Beer, C.; Yeap, B.; Hankey, G.; Flicker, L.; Almeida, O. (2012)
The main purpose of this study was to determine the most robust predictor of mortality among global self-rated health (SRH), time-comparative SRH or a combination of both measures. We also sought to determine factors associated with global SRH and time-comparative SRH measures. A prospective cohort study of 5583 community-dwelling older men aged 70 years or over living in Perth, Western Australia, was used. Older age, depressive symptoms, low social support, sensory impairment, presence of pain, and high Charlson score index were associated with both SRH measures. Global and time-comparative SRH were independent predictors of all-cause mortality (adjusted hazard ratio, HR = 1.24 vs. 1.41 respectively); and the risk of death was almost doubled in those with both negative global SRH and perception of worsening health over the preceding 12 months (adjusted HR 1.98, 95%CI 1.58-2.47). In this group, the rate of death was especially high during the initial four years of follow up. We concluded that the two measures of SRH are likely to reflect the same domains of health, and the simultaneous use of both measures is the best predictor of short to medium term mortality. © 2012 Elsevier Ireland Ltd.